Racial harmony through imaginative creativity in Wilson Harris’ Palace of the Peacock - Deisamisumer, (The Creative Launcher, 2018)
Racial harmony lies at the heart of Harris’ narratives and it gained him recognition as a writer who creates a new form in his novels by bringing the reconciliation among races through creative imagination. As a Guyanese writer, Harris’ characters represent the multi-ethnic make-up of Guyanese society which consists of a mixture of races such as African, Amerindian, Portuguese and European. This paper seeks to study Harris’ greatest work , Palace of the Peacock which is the core of the author’s imagination in bringing unity among races through the consciousness of imagination while examining the central theme of the novel, ideal of unity – unity which is free of cultural and racial ties, embodies a new state of consciousness. After analysing the central theme of the novel an attempt will be made to demonstrate Harris’ ability for positive approach in desiring for “Golden Age” where there is a sense of “Oneness” among races and nations with reference to Palace of the Peacock.